Home range, movement and habitat selection of dholes (Cuon alpinus) in Khao Yai National Park, Thailand - ronglarp - sukmasuang; WARONG SUKSAVATE; NUCHARIN SONGSASEN; NORASET KHIOWSREE; KHWANRUTAI CHARASPET; MANANYA PLA-ARD; YUWALUK CHANACHAI; WARISARA THOMAS; KHANCHIT SRINOPAWAN (Society for Indonesian Biodiversity, 2020)
Abstract. Sukmasuang R, Suksavate W, Songsasen N, Khiowree N, Charaspet K, Pla-ard M, Chanachai Y, Thomas W, Srinopawan K. 2020. Home range, movement and habitat selection of dholes (Cuon alpinus) in Khao Yai National Park, Thailand. Biodiversitas 21: 5915-5926. This study aimed to examine the home range, movement and habitat selection of dholes (Cuon alpinus) in Khao Yai National Park from January 2017 to September 2019 with the objective of studying their movement, diel activity and habitat selection. Based on Autocorrelated Kernel density home range estimation, the results showed that the average home range size of the adult female dhole was 64.6  km2, while the adult male dhole had an average home range size of 132.9 km2. It was found from the monthly analysis that the home range size varied by animal gender and the period of their denning and parenting time. It was also found that the distance traveled by the female dhole was 10.2 km/day, while the male dhole traveled around 19.3 km/day. The overall analysis discovered that the dholes were most active during dawn and dusk. Further, the level of activity increased from May onwards. The grassland and mixed deciduous habitat types significantly affected the selection of the dholes. Case-control linear logistic regression analysis between the distance of the location and habitat types was extremely and positively significant with grassland, which signified the high activity of dhole in the grassland. However, the result was negative with mixed deciduous forest, which was the habitat of the dhole. Autocorrelation functions demonstrated high activity occurred during the early morning and after sunset, which showed that the dholes could adapt for survival in the area, even with recreational activities in the park. The results of this study could contribute to knowledge concerning the species’ movement for long-term species management and conservation.